The practice of public diplomacy confronting challenges abroad - Rugh, William A. (Palgrave Macmillan series in global public diplomacy, 2011)
The conduct of public diplomacy is carried out as much abroad, by Foreign Service Officers (FSOs) stationed at U.S. embassies, as it is in Washington. This book focuses on what FSOs do in actual practice in field operations